Sigmoid volvulus during pregnancy: A case report and literature review (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Sigmoid during in pregnancy is the most common cause of intestinal obstruction. Despitethis, diagnosis remains the largest challenge. The diagnosis of sigmoid volvulus in pregnancy is oftendelayed because the symptoms mimic typical pregnancy-associated complaints. Clinical examination isusually limited because of the gravid uterus, and radiological evaluation presents another challengebecause of the risks of teratogenicity to the fetus, especially in the first trimester. Delays in diagnosisinvariably lead to ischemia, necrosis, and colon perforation, and prompt surgical intervention isnecessary to minimize maternal morbidity and fetal mortality.Case presentation: A 36-year-old para 4+0 gravida 5 presented initially at 29+1 weeks of gestation withabdominal symptoms. A diagnosis of acute gastritis and pyelonephritis was made, and the patient wasallowed home. She later presented with severe abdominal pain and vomiting, after which a diagnosis ofsigmoid volvulus was made at 30+5 weeks of gestation. The patient underwent laparotomy where thevolvulus was detorted. However, she experienced fetal demise in utero two days after the laparotomy.She was induced into labor and expelled the fetus.Conclusion: Sigmoid volvulus complicating pregnancy is rare. However, when it occurs, it may lead toconsiderable maternal and fetal morbidity and mortality. In patients who present with abdominal pain,distension, and absolute constipation, a high index of clinical suspicion is required for prompt diagnosis.Early diagnosis and appropriate surgical intervention are crucial to improve maternal and fetal outcomes,as shown in this case.